Content Analysis of Over-the-Counter Hearing Aid Reviews - Stolyar, Alisa; Katz, Jamie; Dymowski, Catherine; Lyons, Tierney; Parthasarathy, Aravind; Bharadwaj, Hari; Mormer, Elaine; Palmer, Catherine; Wang, Yanshan (AMIA Summits on Translational Science proceedings, 2025)
Hearing loss is a prevalent and impactful condition that affects millions globally. In 2022, the U.S. Food and Drug Administration (FDA) approved over-the-counter (OTC) hearing aids for individuals with mild to moderate hearing loss, establishing a distinct category separate from prescription hearing aids. This regulatory change may leave some patients, particularly those unfamiliar with hearing aids, without medical guidance in their decision-making process. To address this, our team developed the CLEARdashboard (Consumer Led Evidence - Amplification Resources dashboard) as an educational platform to assist users in comparing the technical specifications of various OTC hearing aids. In this study, we proposed a new key feature on the CLEARdashboard that is to utilize Natural Language Processing (NLP) methods to analyze product reviews from two prominent hearing aid online retailers. Analyzing product reviews using NLP is particularly helpful because these reviews often contain detailed, real-world insights into the performance and usability of hearing aids that may not be captured in technical specifications alone. We used NLP techniques in the automatic summarization of large volumes of user feedback into concise "pros and cons" lists, providing patients with a clearer understanding of the strengths and limitations of each device. This approach saves patients from manually sifting through extensive reviews and helps them make informed choices based on aggregated consumer experiences. The generated summaries were validated by three human evaluators to ensure the most comprehensive and reliable method of presenting this information, enhancing the decision-making process for individuals selecting OTC hearing aids.